Human-centered software engineering 4th International Conference, HCSE 2012, Toulouse, France, October 29-31, 2012, proceedings - Conference on human-centered software Engineering (Programming and software engineering, 2012)
This book constitutes the refereed proceedings of the 4th International Conference on Human-Centered Software Engineering, HCSE 2012, held in Toulouse, France, in October 2012. The twelve full papers and fourteen short papers presented were carefully reviewed and selected from various submissions. The papers cover the following topics: user interface design, examining the relationship between software engineering and human-computer interaction and on how to strengthen user-centered design as an essential part of software engineering process.